Fabrication and characterization of electrospun polymer sheets as potential wound dressing material - Yoo, Yeu Cian (2017)
The history of wound dressings spans from ancient to modern times. Extensive research has been done on producing an ideal wound dressing. Electrospinning, being a well-established technique, is an appealing method to create a non-woven fibrous structure which can potentially be used as a wound dressing material due to its unique properties like high surface area to volume ratio. We investigated the electrospun sheet of polymer blend solution, which consists of sodium alginate (SA) and poly-ethylene oxide (PEO) at different ratios. Optimization of the electrospinning process was done, followed by observation under scanning electron microscope (SEM). The addition of surfactant, Triton X-100, exhibited easier formation of fibers. Subsequently, the prepared electrospun sheet was characterized by carrying out cytotoxicity test and water absorption test. Using WST-1 assay, results showed that all electrospun samples do not provoke RAW 264.7 macrophage activation. On top of that, the electrospun samples have high water absorption ability in general, regardless of their composition ratio. These results help us to elucidate the suitability of electrospun SA/PEO as a wound dressing material. This experiment can be further explored by using more polymer blend solution at different ratios to confirm the trend. A larger sample size would also better illustrate the results. These findings may provide further insights on the potential candidate to create an ideal wound dressing in the near future.